Pengaruh Beban Kerja dan Stres Kerja yang Dimediasi oleh Burnout terhadap Perilaku Cyberloafing di Departement R&D PT. Kalbe Farma Tbk - Juniar, Robbi; Arijanto , Agus (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2024)
This research aims to ascertain the effect of burnout-mediated cyberloafing behavior on employee performance, this study will examine workload and work stress. 165 workers in PT. Kalbe Farma TBK's R&D Department made up the study's population. Based on a saturated sample, 165 employees made up the sample that was used. Convenience sampling is used in the sampling process. A questionnaire serves as the study instrument in this survey-based data collection method. A questionnaire serves as the study instrument in this survey-based data collection method. Partial Least Square is used in the data analysis process. This study demonstrates the strong correlation between workload behavior and cyberloafing habit. Cyberloafing behavior is significantly impacted by job stress. Burnout is significantly impacted by workload. Burnout is significantly impacted by job stress. Cyberloafing is significantly impacted by burnout. Both directly and indirectly, through burnout as a mediating variable, workload affects cyberloafing. Workplace Stress acts as a mediator variable between Cyberloafing and Burnout.